2017
DOI: 10.2217/fmb-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profile of Mycobacterium Tuberculosis after Eupomatenoid-5 Induction Reveals Potential Drug Targets

Abstract: Some of the differentially expressed proteins have the potential to be drug targets such as citrate synthase (Rv0896), phosphoglycerate kinase (Rv1437), ketol-acid reductoisomerase (Rv3001c) and ATP synthase alpha chain (Rv1308).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…mgf without summing the scans by the Mascot Distiller software (version 2.3.2.0; Matrix Science, United Kingdom) and searched against the knowledgebase UniProtKB using the Mascot software (version 2.4.0; Matrix Science, United Kingdom). For the search, the following parameters were considered: taxonomy Salmonella and all entries (separately), monoisotopic mass, trypsin, allowing up to one missed cleavage site, peptide charge +2, +3 and +4, fixed modification for carbamidomethylation of cysteine residues and variable modification for oxidation of methionine residues, peptide and MS/MS tolerance equal to 0.1 Da [ 53 55 ], ESI-QUA-TOF for instrument. The proteins identifications by Mascot software were validated and the proteins were quantified by Scaffold software (version 4.7.2; Proteome Software, USA).…”
Section: Methodsmentioning
confidence: 99%
“…mgf without summing the scans by the Mascot Distiller software (version 2.3.2.0; Matrix Science, United Kingdom) and searched against the knowledgebase UniProtKB using the Mascot software (version 2.4.0; Matrix Science, United Kingdom). For the search, the following parameters were considered: taxonomy Salmonella and all entries (separately), monoisotopic mass, trypsin, allowing up to one missed cleavage site, peptide charge +2, +3 and +4, fixed modification for carbamidomethylation of cysteine residues and variable modification for oxidation of methionine residues, peptide and MS/MS tolerance equal to 0.1 Da [ 53 55 ], ESI-QUA-TOF for instrument. The proteins identifications by Mascot software were validated and the proteins were quantified by Scaffold software (version 4.7.2; Proteome Software, USA).…”
Section: Methodsmentioning
confidence: 99%
“…[6] Transposonm utagenesis experiments have confirmed that KARI is an essential gene in Mt [7] and is also essential in asymptomatic Escherichia coli found in urine. [8] In addition, ap roteomic profile of Mt after eupomatenoid-5 induction revealed KARI as ad rug target, [9] and deletion mutation experiments in Fusarium graminearum demonstrated that KARI is essentialf or full virulence in this plant pathogen that causes head blight. [10] KARI is ab i-functional enzyme catalyzing an isomerization reactiona nd an NAD(P)H-mediated reduction.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, KARI has also emerged as a promising drug target; [6,8,16,17] in both Mycobacterium tuberculosis ( Mt ) and uropathogenic Escherichia coli ( Ec ), KARI has been shown to be essential for growth and survival [16,17] . Consequently, diverse compounds that significantly inhibit KARI have recently been developed as potential anti‐microbial drug candidates [8,18–22] …”
Section: Introductionmentioning
confidence: 99%